Impacts of Aggregator Business on Farmers’ Income - Siti Jahroh; Janita S. Meliala (Jurnal Manajemen & Agribisnis, 2021)
Agricultural produces pass a long journey from the farms up to the end consumers. With the advancement of information technology, aggregator businesses have emerged to shorten the long distribution chain. Therefore, farmers as producers can access information both on prices received by consumers and the characteristics of products demanded by consumers. This study aims to (1) explain the distribution chain mechanism through the aggregator business, and (2) analyze the impact on farmers who join the aggregator business distribution chain. There were 12 aggregator businesses and 36 farmers were interviewed as respondents from February to April 2019 using the purposive sampling method. The analysis was conducted using a descriptive approach and a paired sample t-test was carried out to see the impact of the existence of an aggregator on farmers. The results showed that the distribution chain through the aggregator business was shorter compared to the conventional one in which farmers had specific contracts or agreements with the aggregator business. The impact on farmers who join the aggregator business distribution chain is receiving higher prices, leading to increase farmers' income, transparency in prices where farmers know the selling prices at the consumer level, and farmers know consumer preferences for the products. It is expected that farmers will be able to produce better agricultural produces according to consumer preferences as well as to increase farmers' income. Keywords: distribution chain, price, product preferences, transparency